ZAKAT SEBAGAI SUMBER PENINGKATAN KEMANDIRIAN FISKAL DI PROVINSI ACEH - Hasibuan, Diana Febriani; Miksalmina, Miksalmina (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
This study aims to determine the contribution of zakat and economic growth in increasing fiscal independence in Aceh Province in 2015-2019. The type of research used is descriptive quantitative research with multiple linear regression method and choose a random effects model approach (Random Effect).The data used is secondary data, consisting of zakat realization, economic growth, and fiscal independence. The sourced of data is from the Aceh Supreme Audit Agency (BPKA), the Central Statistics Agency (BPS) of Aceh Province, and the Supreme Audit Agency of the Republic of Indonesia (BPK RI). This study indicate that zakat and economic growth positively and significantly effect increasing fiscal independence in Aceh Province in 2015-2019. Local governments can increase fiscal independence through socialization to the community to distribute their zakat through Baitul Mal and local governments need to continue to maintain the level of economic growth through increasing the production of goods and services in Aceh Province.